2016
DOI: 10.1212/cpj.0000000000000214
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and outcomes of stroke during pregnancy and the postpartum period

Abstract: Compared with nonpregnant women of the same age group, women with PAS had fewer vascular risk factors. Cerebral venous thrombosis and RCVS were more common in PAS, most of which occurred postpartum. These results provide further evidence for the unique pathophysiology of pregnancy-related stroke, raising important questions for future investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…Stroke is also rare in pregnancy and the puerperium, complicating 34 out of 100,000 deliveries [6], with 75% occurring postpartum [7]. The differential diagnosis for pregnancy-associated stroke includes preeclampsia/eclampsia, cardioembolic disease, antiphospholipid syndrome, inherited thrombophilia, and pregnancy-related hypercoagulability [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stroke is also rare in pregnancy and the puerperium, complicating 34 out of 100,000 deliveries [6], with 75% occurring postpartum [7]. The differential diagnosis for pregnancy-associated stroke includes preeclampsia/eclampsia, cardioembolic disease, antiphospholipid syndrome, inherited thrombophilia, and pregnancy-related hypercoagulability [7].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis for pregnancy-associated stroke includes preeclampsia/eclampsia, cardioembolic disease, antiphospholipid syndrome, inherited thrombophilia, and pregnancy-related hypercoagulability [7]. Other stroke risk factors include migraine headaches, hypertension, diabetes, smoking, advanced maternal age, and African American race [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several vital organs bear the brunt of this syndrome resulting in cortical blindness, cerebral oedema, haemorrhagic stroke, liver rupture and subarachnoid haemorrhage. [2][3][4][5] Major consequences of these organ damages are furthermore complicated by preeclampsia to a great extent. Elevated liver enzymes and serum bilirubin signify compromised hepatic function whereas decreased platelet count and increased haemolysis indicate increased risk for bleeding disorders for these particular varieties of preeclampsia patients.…”
Section: Introductionmentioning
confidence: 99%
“…If not recognised at early stage, the outcome of this syndrome is grim due to development of neurological complications like strokes or other neurological deficits. [5] Regarding the diagnosis and extent of symptoms, HELLP syndrome has been significantly inconsistent till now. Since Sibai [6] proposed strict criteria for the diagnosis of the "true HELLP syndrome", it has been observed that many women with severe preeclampsia may have laboratory abnormalities such as isolated haemolysis or low platelet count or elevated liver enzymes, without the complete HELLP syndrome.…”
Section: Introductionmentioning
confidence: 99%